Records of Thysanoptera Species in Greece - Deligeorgidis Ρ. Ν. (ENTOMOLOGIA HELLENICA, 2002)
Aiming to the registration of Thysanoptera species, thrips collections had taken place from field, greenhouse crops and weeds in 16 regions of Greece during 1991 and 1994. In total, 26 Thysanoptera species were found in 34 different crops and weeds, belonging to the families Aeolothripidae, Thripidae and Phlaeothripidae. Among the species collected, Tenothrips frici is recorded for first time in Greece.